Student Identity and Guided Inquiry Learning in Junior High School Students: A Correlation Analysis - Kiki Septaria; Khoirotun Nissak; Siska Ayu Wulandari (Jurnal Penelitian Pendidikan IPA, 2023)
This study depends on why it's important for an examination of students' scientific identities to demonstrate that a student is scientifically capable of identifying and resolving issues in the form of natural occurrences. The purpose of this research is to determine the rise in scientific identity utilizing the guided inquiry learning model, as well as the closeness of the variable link between scientific identity and the guided inquiry learning model. This study employed a one-group pre-test and post-test design with a quantitative approach and a population or sample through purposive sampling with a sample size of 60 students. This study was conducted Turi Lamongan State Junior High School. A scientific identity questionnaire exam and a cognitive ability test were used to collect data for this investigation. In this study, N-gain was used to see a rise in the science identity questionnaire and cognitive ability tests, followed by a correlation test to establish the degree of closeness between science identity and the guided inquiry learning model. This study's findings are as follows: 1) improving scientific identity through guided inquiry learning 2) Scientific identity and the guided inquiry learning methodology are linked.